Pellerin's craniofacial distractor: A boon in low-resource setting - Sunil Richardson; Phillipe Pellerin; Rakshit Khandeparker; Shreya Krishna (Wolters Kluwer Medknow Publications, 2018)
Aim: The aim is to show the use of a novel Pellerin's distractor in the correction of midfacial and mandibular deformities. Materials and Methods: A total of ten patients were included in the study. Among the ten patients, two presented with Apert syndrome, three with Crouzon syndrome (CS), three with hemifacial microsomia, one with temporomandibular joint ankylosis, and one presented with Pfeiffer syndrome. All cases were treated by the Pellerin's distractor. All patients were followed for a minimum of 1 year. Results: Two patients were lost to follow-up. All the remaining patients achieved satisfactory correction of their deformity. The average amount of advancement achieved was 37.5 mm (32-50 mm). No serious complications were seen in any patient. Pin tract scarring was the most common complication seen in six of the patients. Conclusion: The Pellerin distractor can be used in both the midface and the mandible for correction of the deformities. The device is constructed using easily available hardware that is also resusable. This makes it a cost effective alternative to the currently available distractor appliances, especially for a low-resource setting.